Effects of attapulgite-supported transition metals catalysts on glycerol steam reforming for hydrogen production. (8th November 2018) - Chen, Mingqiang; Zhou, Zhongshan; Wang, Yishuang; Liang, Tian; Li, Xiaojing; Yang, Zhonglian; Chen, Minggong; Wang, Jun
Abstract: The attapulgite supported transition metals (Ni, Cu, Co or Fe) catalysts were prepared by precipitation method at constant loading (10 wt%) and investigated in the glycerol steam reforming reaction for H2 production under 400–750 °C, water/glycerol (W/G) = 3, N2 flow ratio = 0.16 L/min and WHSV = 6.46 h −1 . The as-prepared catalysts were characterized by N2 adsorption-desorption, XRD, H2 -TPR and TEM-EDS. The results shown different active metals presented various crystalline sizes and reduction properties. The experimental results revealed Ni/ATP and Co/ATP catalysts had more active for glycerol steam reforming than Cu/ATP and Fe/ATP catalysts, due to the fact that active metal Ni and Co have superior capacity to promote the necessary CC rupture and facilitate the water gas shift reaction. In addition, the results revealed that CH4 production was favored at low temperatures while CO production was presented at high temperatures, which were induced by the different reaction networks over catalysts. In addition, the stability test shown all catalysts had different various degrees of inactivation, resulting from the sintering of active metals and carbon deposition. The characterizations of XRD, TEM and TG-DTG for spent catalysts revealed the smallest amount of carbon deposited for Cu/ATP, which was attributed to the lowest Cu particle size. Additionally, two different types of carbon was found, namely filamentous carbon for Ni and Co/ATP and encapsulating carbon for Cu and Fe/ATP. Highlights: M/ATP (M = Ni, Cu, Co and Fe) catalysts were prepared by precipitation method. The catalytic performance of all catalysts was investigated in GSR reaction. Ni/ATP and Co/ATP presented the higher glycerol conversion and H2 yield. Active metals of Ni and Co revealed the superior CC breakage and enhanced WGSR. The deactivation mechanism is encapsulating carbon blocks active mental sites.